Supply Chain Performance Analysis in the Cocoa Industry Using SCOR AHP Method: Case Study of PT XYZ in Bali - Girsang, Ruth Maida Demona; I Wayan Gede Sedana Yoga; A. A. P. Agung Suryawan Wiranatha (Cita konsultindo, 2025)
PT XYZ is a cocoa processing company that requires a supply chain performance evaluation, as previous measurements have focused mainly on profit without considering process effectiveness. This study aims to measure supply chain performance using the Supply Chain Operations Reference (SCOR) framework and the Analytical Hierarchy Process (AHP). A total of 30 indicators across the five core SCOR processes were evaluated, weighted using AHP, and priority improvement indicators were identified. The results show a supply chain performance score of 87.46 (Good). Most indicators were in the excellent category; however, several remained low, including forecast accuracy (70.90, good), raw material planning accuracy (19.13, poor), number of trouble machines (66.67, average), and inventory accuracy for finished products (0.00, poor). In addition, the timely delivery performance by suppliers (90.83, excellent) was identified as vulnerable to decline. Improvements focus on low-performing indicators through strategies such as more accurate forecasting, integrated raw material planning systems, scheduled machine maintenance, real-time finished product inventory recording, and inventory coordination with suppliers through safety stock. This study provides a basis for systematic evaluation to enhance supply chain effectiveness and support the company’s operational sustainability.